2016
DOI: 10.1039/c6ra12640e
|View full text |Cite
|
Sign up to set email alerts
|

Precise casting of biomorphic La0.9K0.1CoO3 catalysts derived from pinewood for diesel soot combustion

Abstract: A biomorphic perovskite-type oxide, possessing a large surface area, was successfully fabricated using pinewood as a template. The porous structure prompted catalytic activity towards soot combustion under low temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…For oxygen-only mixtures, the O 2 content varies from 21% as in air ,,,,, to 2.5% in an inert gas . The most common mixture is 5% O 2 in an inert gas, , ,,,, but concentrations up to 10% O 2 are also popular. ,,,, Similarly, for the O 2 + NO mixtures, the oxygen concentration is typically set between 3 and 10%, with the NO concentration between 400 and 3000 ppm. ,,,,, ,,,,,,,, More recently, the effect of SO 2 presence was also investigated.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For oxygen-only mixtures, the O 2 content varies from 21% as in air ,,,,, to 2.5% in an inert gas . The most common mixture is 5% O 2 in an inert gas, , ,,,, but concentrations up to 10% O 2 are also popular. ,,,, Similarly, for the O 2 + NO mixtures, the oxygen concentration is typically set between 3 and 10%, with the NO concentration between 400 and 3000 ppm. ,,,,, ,,,,,,,, More recently, the effect of SO 2 presence was also investigated.…”
Section: Introductionmentioning
confidence: 99%
“…For oxygen-only mixtures, the O 2 content varies from 21% as in air 21,25,29,33,54,73 to 2.5% in an inert gas. 74 The most common mixture is 5% O 2 in an inert gas, 34,[42][43][44]47,48,53,64 but concentrations up to 10% O 2 are also popular.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perovskite-type catalysts are of great interest due to their promising properties, La 0.9 K 0,1 CoO 3 in particular. Liu et al [168] developed La 0.9 K 0,1 CoO 3 catalysts from pinewood, with a high porosity and surface area (total pore volume of 0.050-0.101 cm 3 /g and BET surface area of 84.09-147.97 m 2 /g depending on the treatment of wood, respectively), that reduced soot combustion temperature to 340 • C. To test the catalytic activity of the product, a catalyst: soot solution with a mass ratio of 20:1 was analyzed by a thermal gravimetric analyzer. The result of this analysis showed that the temperature at which 10% of carbon was oxidized was reduced by 59 • C, which confirmed the potential use of La 0.9 K 0,1 CoO 3 catalysts in reducing soot combustion emissions.…”
Section: D) Other Reactionsmentioning
confidence: 99%
“…23,24 Even though the specific surface area of original wood fiber is less than 1 m 2 /g, the catalytic materials with wide pore size distribution and high specific surface area can be prepared taking wood as template. 25 Ming Zhou et al prepared biomorphic porous zinc oxide with wood fiber as template, which proved the specie of wood template and sintering temperature played vital roles in the pore size distribution, specific surface area, and pore volume of the product. 26 Our previous studies showed that La 0.8 Ce 0.2 Fe 0.3 Co 0.7 O 3 can achieve the four-way purification of PM, NO x , CO and HC emitted by automobile exhausts, and the purification efficiency are 95%, 92%, 100%, and 94%, respectively.…”
Section: Introductionmentioning
confidence: 99%